Non-Financial Reporting and Compliance Control - T. Yu. Serebryakova (Учёт. Анализ. Аудит)
The article is devoted to non-financial reporting (NFR) and problematic aspects of confirming its quality, truthfulness and, most importantly, the objectivity of the NFR. Despite the fact that there is an increase in the number of organizations that are compiling the NFRs, the information there does not inspire confidence in a reasonable user. There are at least two aspects: the first is the reliability and validity of the information presented in it, and the second is the problem concerning its assurance, which arises due to both the standardisation of the reporting itself and the procedure for its verification. The purpose of the study is to develop an understanding by the state, business, and society of the degree of public necessity of the NFR, as well as the existing experience and possibilities of its regulation and verification. In the process of the research such general scientific methods of cognition as systematic approach, logical generalisation, legal and linguistic analysis, and hypothesis were used. It is possible to overcome many problems of the NFR by standardising the procedures for its preparation at the international level, while the problems of verification of the non-financial reporting can be identified separately, since it can be carried out not only under the auspices of the International Federation of Accountants, which follows from the combination of IFRS — ISA, but also by professional communities, as well as directly interested companies and their associations. The EU experience is interesting, which has advanced the regulation of the NFR and its authorisation to a new level, however, there is doubt about whether the NFR is really necessary. For the Russian Federation, NFR data can be compiled at all levels of the country’s economy and management within the framework of statistical accounting, if the problem of determining the real consumer and operator (administrator) of such information is solved. Data verification can be carried out within the framework of statistical accounting, which correlates with accounting. To this end, it is possible and necessary to create domestic standards for auditing statistical reporting, which, by the way, is not certified by anyone, but trust in it is invariably higher than in the NFR, precisely due to consistency with accounting (financial) reporting.